If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10 + -2q = -2 + q Solving 10 + -2q = -2 + q Solving for variable 'q'. Move all terms containing q to the left, all other terms to the right. Add '-1q' to each side of the equation. 10 + -2q + -1q = -2 + q + -1q Combine like terms: -2q + -1q = -3q 10 + -3q = -2 + q + -1q Combine like terms: q + -1q = 0 10 + -3q = -2 + 0 10 + -3q = -2 Add '-10' to each side of the equation. 10 + -10 + -3q = -2 + -10 Combine like terms: 10 + -10 = 0 0 + -3q = -2 + -10 -3q = -2 + -10 Combine like terms: -2 + -10 = -12 -3q = -12 Divide each side by '-3'. q = 4 Simplifying q = 4
| .03x+.04(4y)=760 | | Log*4*(x+5)=log*4*(2x-7) | | r+20=16 | | cos(39)=x/2 | | 11/v=8/5 | | -2(3S-5)-10=-3(9S+3)-4 | | y=5x^2-45x+100 | | 3w^2-2w+2=0 | | 8x+28-8x=28 | | 42=2/3x | | 7x-1=9x-15 | | X/12-46=6 | | -6u+46=6u | | x-(0.2x)=0.6 | | 5/3u=25 | | -(5X+4)-(-4X-9)=13 | | 12y^2+23y+5= | | 9v^2-30+25=0 | | 4+9k=-5 | | 6w-2=2w+58 | | 9v^2-30v-25=0 | | 8x=16/7 | | D=26/pi | | http://media1.acellus.com/Library/00001022_223_A1.gif | | 56+8m=128 | | 4y^2+17y-15= | | 14y+1=1y+27 | | n-17=-13 | | 17n-70=168 | | 8x-10=8x-6 | | 42=4x+2x | | 4a+1=1a+25 |